A multicontinental dataset of butterfly thermal physiological traits - Sarah E. Diamond; Carmen R. B. da Silva; Osmary A. Medina-Báez (Scientific Data)
Abstract Butterflies serve as key indicators of climate change impacts such as shifts in emergence timing and shifts in geographic range and distribution. However, the development of commonly used ecological forecasts based on butterfly physiological tolerance of temperature change has lagged behind that of other taxonomic groups. Here, we provide a series of related datasets comprising butterfly thermal physiological traits to enable such forecasts. We compiled data from the literature on butterfly heat and cold tolerance (critical thermal maxima and minima) for 117 species as well as heat resistance (knockdown time) for 45 species. We also present a new dataset comprising heat and cold tolerance and thermal sensitivity of metabolic rate of 28 common North American butterfly species. We envision these data to not only provide foundations for contemporary ecological forecasts of vulnerability to recent climate change, but also to aid in our understanding of butterfly ecology and evolution over historical timescales.